Inflammatory Response and Acute Phase Proteins in the Transition Period of High-Yielding Dairy Cows - Trevisi, Erminio; Amadori, Massimo; Archetti, Ivonne; Lacetera, Nicola; Bertoni, Giuseppe (IntechOpen, 2011)
None